2021
DOI: 10.1101/2021.05.27.446031
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Late-in-life treadmill-training rejuvenates autophagy, protein aggregate clearance, and function in mouse hearts

Abstract: There is evidence for a progressive decline of protein quality control mechanisms during the process of cardiac aging. This enables the accumulation of protein aggregates and damaged organelles that contribute to age-associated cardiac dysfunction. Macroautophagy (referred to as autophagy) is the process by which post-mitotic cells such as cardiomyocytes clear defective proteins and organelles. We hypothesized that late-in-life exercise training improves autophagy, protein aggregate clearance, and function tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
1
0
0
Order By: Relevance
“…Furthermore, in the study of No et al, 37 eight-weeks of treadmill exercise in aging rats resulted in reduced Pink, Parkin, and LC3 II protein expression, and increased mitochondrial oxygen respiration, hydrogen peroxide emission, and calcium (Ca 2+ ) retention capacity in the myocardium, which indicated that long-term exercise also reduced aging induced mitochondrial dysfunctions and excessive autophagy in the heart. Similar conclusions were also found in the study of Cho et al 38 : long-term treadmill training intervention mitigated excessive autophagic flux and improved protein aggregate clearance as well as damaged contractile performance in mouse hearts.…”
Section: Exercise-mediated Autophagy In Cardiovascular Diseasessupporting
confidence: 88%
“…Furthermore, in the study of No et al, 37 eight-weeks of treadmill exercise in aging rats resulted in reduced Pink, Parkin, and LC3 II protein expression, and increased mitochondrial oxygen respiration, hydrogen peroxide emission, and calcium (Ca 2+ ) retention capacity in the myocardium, which indicated that long-term exercise also reduced aging induced mitochondrial dysfunctions and excessive autophagy in the heart. Similar conclusions were also found in the study of Cho et al 38 : long-term treadmill training intervention mitigated excessive autophagic flux and improved protein aggregate clearance as well as damaged contractile performance in mouse hearts.…”
Section: Exercise-mediated Autophagy In Cardiovascular Diseasessupporting
confidence: 88%